Anisotropic electrical resistance of proton exchange membrane fuel cell transport layers as a function of cyclic strain. (20th April 2016) - Todd, Devin; Bennett, Scott; Mérida, Walter
Abstract: We report on the three-dimensional electronic resistance of proton exchange membrane fuel cell porous transport layers (PTLs) as a function of cyclic mechanical compression. Through-plane data are reported as total area resistance (i.e. inclusive of contact resistance contributions), whereas in-plane data are reported as resistivity measurements with resolved anisotropy. In-plane resistivities are acquired via a square four-point-probe arrangement (4PP), which unlike linear 4PP arrangements, can resolve the anisotropy. Results are presented for SGLSigracet 25 BA. Both through-plane and in-plane data exhibit unique profiles for the initial compressive loading. These are followed by consistent trajectories for subsequent loading cycles, which is in correspondence to material plastic deformation. Plastic deformation damage to PTLs may occur during cell manufacture; to the possible detriment of deployed stack performance. We outline means by which our method can be adapted for on-line monitoring of PTLs as part of a manufacturing quality assurance programme. Highlights: We report transport layer electrical resistance versus cyclic mechanical strain. Material anisotropy through-plane and within in-plane is captured. Sheet resistance may estimate plastic set and have quality assurance utility.